Penerapan Algoritma Elias Delta Codes Dalam Kompresi File Teks - Rizky, Nadia Fariza; Nasution, Surya Darma; Fadlina, Fadlina (Forum Kerjasama Pendidikan Tinggi, 2020)
File size or large files are not only a problem in terms of storage, but also another problem when communication between computers. Data usage with a larger size will take longer transfer times compared to data that has a smaller size. Therefore to overcome this problem you can use data compression. Seeing the compression of data compression, data compression is needed that can reduce the size of the data, so that it gains the advantage of reducing the use of external storage media space, accelerating the process of transferring data between storage media, data utilization used in this study is the elias delta codes algorithm. Compression is a method used to reduce the bit or data from the original result to a new result. Where this compression will be applied into the algorithm, the elias delta codes algorithm. After getting the results of the compression it will be designed into Microsoft Visual Studio 2008